The Plastic Surgery In-service Training Examination: An In-depth Reference Analysis - Jesse D. Meaike, MD; Malke Asaad, MD; Sean Cantwell, MD; Rami Elmorsi; Mohamed Sobhi Jabal; Steven L. Moran, MD (Plastic and Reconstructive Surgery, Global Open, 2021)
Background:. The goal of this study was to characterize the references provided as supporting evidence of the Plastic Surgery In-service Training Examination (PSITE) syllabi, including those on the novel “core surgical principles” section. Methods:. We analyzed the references from five consecutive PSITE Examination syllabi (2016–2020). We collected the following information from each question: question section, total number of references, and source of publication of each reference. Results:. We analyzed 1250 questions and 3436 references. Plastic and Reconstruction Surgery was overall the most frequently referenced journal followed by Journal of Hand Surgery (American Volume) and Annals of Plastic Surgery. The most commonly referenced textbooks were Plastic Surgery (by Neligan), Green’s Operative Hand Surgery, and Grabb and Smith’s Plastic Surgery. Regarding the “core surgical principles” section, Plastic and Reconstruction Surgery remained the most frequently cited journal, followed by the Journal of the American Medical Association, New England Journal of Medicine, Annals, and Aesthetic Surgery Journal. “Core surgical principles” contained the largest number of unique journals (n = 209) among all test sections. Within the “core” section, Statistics in Medicine was the most frequently referenced textbook followed by Grabb and Smith’s Plastic Surgery. Conclusions:. The main plastic surgery texts and literature were used to support approximately half of the answers within the “core surgical principles” section. The references within this section originated from the largest number of different journals, thus highlighting the breadth and variety of this content and the challenges in preparing for this section.